2005
DOI: 10.1063/1.2067711
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the quantum-confinement effect in individual Ge nanocrystals on oxidized Si substrates using scanning tunneling spectroscopy

Abstract: Scanning tunneling spectroscopic studies revealed the quantum-confinement effects in Ge nanocrystals formed with ultrahigh density (>1012cm−2) by Ge deposition on ultrathin Si oxide films. With decreasing crystal size, the conduction band maximum upshifted and the valence band minimum downshifted. The energy shift in both cases was about 0.7 eV with the size change from 7 to 2 nm. This shows that the energy band gaps of Ge nanocrystals increased to ∼1.4eV with decreasing size. This size dependence can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
107
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 121 publications
(112 citation statements)
references
References 16 publications
5
107
0
Order By: Relevance
“…The shift of E h−GS shows good consistency on the aforementioned PES results after shifting by an adequate energy reference [30]. A gradient of an E h−GS -E e−GS plot was fitted as 1.02 ± 0.28 which is consistent to the expected value for intrinsic Ge nanodots (∼ 1) [42].…”
Section: B Scanning Tunneling Spectroscopymentioning
confidence: 52%
See 1 more Smart Citation
“…The shift of E h−GS shows good consistency on the aforementioned PES results after shifting by an adequate energy reference [30]. A gradient of an E h−GS -E e−GS plot was fitted as 1.02 ± 0.28 which is consistent to the expected value for intrinsic Ge nanodots (∼ 1) [42].…”
Section: B Scanning Tunneling Spectroscopymentioning
confidence: 52%
“…Nakamura and coworkers evaluated "VBM" and "conduction band minima (CBM)" of individual epitaxial nanodots by STS at RT [42]. They reported that the "VBM" downshifted and the "CBM" shifted upwards as the dot size decreases, which should be attributed to a sign of the quantum size effect.…”
Section: B Scanning Tunneling Spectroscopymentioning
confidence: 99%
“…[8,9] Generally, these physical methods produce particles with substantial size distributions, undesirable for applications that exploit size-dependent electronic properties. Bottom-up solution-phase synthetic chemistry methods offer better control of the size and shape of the nanoparticles, but often do not provide the good crystallinity required for many applications, and require the use of longchain ligands and surfactants to stabilize the particle surface and control growth.…”
Section: Synthesis Of Nanoamorphous Germanium and Itsmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] The germanium sources in these investigations are usually the germanium halides, GeX n , or organogermanes [23,24] in which the Ge center is either in the 4 + or 2 + oxidation state (e.g., GeCl 4 , GeBr 4 , GeI 2 ), and long-chain phosphines and alkenes are often used as surface protection ligands for nanoparticle stabilization. The reducing agents used in these investigations are usually the strong ones, such as LiAlH 4 , NaBH 4 , sodium, sodium naphthalide, butyllithium, and Ge Zintl salts.…”
Section: Synthesis Of Nanoamorphous Germanium and Itsmentioning
confidence: 99%
“…Nakamura 37 studied the upshift of the conduction band and downshift of valence band with decreasing crystal size. The energy shift in both cases was about 0.7 eV with the size change from 7 to 2 nm.…”
Section: (B)mentioning
confidence: 99%